Iterative methods for solving fixed-point problems with nonself-mappings in Banach spaces - Yakov Alber; Simeon Reich; Jen-Chih Yao (Abstract and Applied Analysis)
We study descent-like approximation methods and proximal methods of the retraction type for solving fixed-point problems with nonself-mappings in Hilbert and Banach spaces. We prove strong and weak convergences for weakly contractive and nonexpansive maps, respectively. We also establish the stability of these methods with respect to perturbations of the operators and the constraint sets.